Ponatinib‐induced neutrophilic panniculitis. (8th April 2014) - Zhang, May; Hassan, Khaled M.; Musiek, Amy; Rosman, Ilana S.
<x xml:space="preserve">Abstract</x> Ponatinib is a bcr‐abl tyrosine‐kinase inhibitor (TKI) used to treat resistant and refractory chronic myeloid leukemia and Philadelphia chromosome‐positive acute lymphoblastic leukemia that express bcr‐abl. Neutrophilic panniculitis has been described in rare cases of patients on other TKIs in the same class as ponatinib. We present the first case of neutrophilic panniculitis following treatment with ponatinib and summarize the other cases of panniculitis caused by TKIs.